Ciclos bioquímicos en un ecosistema forestal de los Andes Occidentales de Venezuela, 2: Producción y descomposición de los residuos vegetales. - Fassbender, H.W; Grimm, U. (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
Litter production (tree stands, each 12 collectors; sampling every two weeks) and litter decomposition (samples of leaves and branches exposed to enviroment, collection every two months) were studied in a montane forest ecosystem of the Venezuelan Andes. The total litter production reached an average of 6.97 Oa per year and was distributed as follows: leaves 3.38 t/ha per year = 48%, branches 2.27 t/ha per year = 33%, flowers and fruits 1.09 t/ha per year =16%, epiphytic plants 0.23 t/ha per year = 3%. The variation of coefficients of leaves, flowers and fruits were low (14 and 26% ) and that for branches was high (64%). The annual renewal of leaf-biomass reached 73%. The litter production in form of roots and dead wood yielded 14 and 4.8 t/ha/year. The transfer of chemical elements with litter depends on the specific soil conditions For N, P and K, values of 69.4 and 33 kg/ha/year were recorded. The decomposition of litter is linear. Total decomposition of leaf litter occurs after 20 months exposition. Branches require 12 1/2 years to disappear. A coefficient of organic matter transformation according to Jenny was calculated and compared with other tropical forest ecosystems.